2004
DOI: 10.1002/jnr.20144
|View full text |Cite
|
Sign up to set email alerts
|

Caloric restriction augments brain glutamic acid decarboxylase‐65 and ‐67 expression

Abstract: The ketogenic diet is a very low-carbohydrate, high-fat diet used to treat refractory epilepsy. We hypothesized that this diet may act by increasing expression of glutamic acid decarboxylase (GAD), the rate-limiting enzyme in gamma-aminobutyric acid (GABA) synthesis. Thus, we evaluated brain GAD levels in a well-established, seizure-suppressing, rodent model of the ketogenic diet. Because the diet is most effective when administered with a modest ( approximately 10%) calorie restriction, we studied three group… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
48
0
5

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 80 publications
(55 citation statements)
references
References 38 publications
2
48
0
5
Order By: Relevance
“…Another study in rats fed the KD for 3 weeks found increased levels of glutamate and glutamine in the hippocampus, but this was also associated with an overall decrease in the transcripts of genes involved in synaptic transmission ( 48 ). Further, using both mild CR (i.e., 90% of daily energy requirements or 10% CR) and an isocaloric KD, investigators found signifi cant increases in the mRNA expression of both isoforms of GAD (GAD65 and GAD67) in several brain regions and independent of ketogenic effects ( 80 ). Additionally, reduced levels of aspartate were found in a mouse model of ketosis, along with the expected increases in acetyl-CoA, with no change in the levels of GABA and glutamate ( 77 ).…”
Section: Crmentioning
confidence: 96%
“…Another study in rats fed the KD for 3 weeks found increased levels of glutamate and glutamine in the hippocampus, but this was also associated with an overall decrease in the transcripts of genes involved in synaptic transmission ( 48 ). Further, using both mild CR (i.e., 90% of daily energy requirements or 10% CR) and an isocaloric KD, investigators found signifi cant increases in the mRNA expression of both isoforms of GAD (GAD65 and GAD67) in several brain regions and independent of ketogenic effects ( 80 ). Additionally, reduced levels of aspartate were found in a mouse model of ketosis, along with the expected increases in acetyl-CoA, with no change in the levels of GABA and glutamate ( 77 ).…”
Section: Crmentioning
confidence: 96%
“…Cheng et al [35] reported that rats fed a calorie-restricted diet for 7 days show increased expression of various glutamic acid decarboxylase isoforms in selected brain regions, including the superior colliculus and cerebellar cortex. However, the changes in expression were similar whether the animals received an ordinary calorie restricted diet or a high-fat, ketogenic diet, indicating that high fat and ketosis do not have specific effects of glutamic acid decarboxylase expression.…”
Section: Effects Of the Ketogenic Diet On Gaba Synthesismentioning
confidence: 99%
“…Yet another study in rats fed the KD for 3 weeks found increased levels of glutamate and glutamine in the hippocampus, but this was also associated with an overall decrease in the transcripts of genes involved in synaptic transmission [20]. Further, using both mild caloric restriction or CR (i.e., 90% of daily energy requirements or 10% CR) and an isocaloric KD, investigators found significant increases in the mRNA expression of both isoforms of GAD (GAD65 and GAD67) in several brain regions which were independent of ketosis [21]. Additionally, reduced levels of aspartate were found in a mouse model of ketosis, along with the expected increases in acetyl-CoA, with no change in the levels of GABA and glutamate [17].…”
mentioning
confidence: 96%